New generation of organic scintillation materials - Budakovsky, S.V.; Galunov, N.Z.; Grinyov, B.V.; Kim, J.K.; Kim, Y.K.; Tarasenko, O.A. (Functional Materials, 2009)
Organic scintillation materials of the next generation have been designed and prepared, namely, organic polycrystals obtained from finely ground perfect single crystals by pressing and organic composite scintillators obtained by immersing crystalline grains into an optically transparent polymer matrix. The scintillation characteristics of proposed scintillation materials as detectors for short-range ionizing radiation and fast neutrons are discussed. This technology forms the base for production of large area detectors which can be used in devices for environmental radiation control, for security purposes (i.e. at customs to prevent the forbidden entry of fission materials), for various nuclear physical experiments, and in other branches of science and technology. Розроблено органічні сцинтиляційні матеріали нового покоління - органічні полікристали, отримані шляхом пресування зерен структурно-досконалого монокристала, а також органічні композиційні сцинтилятори, виготовлені шляхом введення кристалічних зерен в оптично-прозору полімерну матрицю. Обговорюються сцинтиляційні характеристики запропонованих сцинтиляторів як детекторів короткопробіжних випромінювань та швидких нейтронів. Запропоновано технологія є підгрунтям подальшої розробки органічних детекторів великої площі для вирішення актуальних проблем моніторингу навколишнього середовища, митного огляду, проведення різних ядернофізичних досліджень. Разработаны органические сцинтилляционные материалы нового поколения - органические поликристаллы, полученные прессованием кристаллических зерен структурно- совершенного монокристалла, а также органические композиционные сцинтилляторы, изготовленные путем введения кристаллических зерен в оптически-прозрачную полимерную матрицу. Обсуждаются сцинтилляционные характеристики предложенных сцинтилляторов как детекторов короткопробежного излучения и быстрых нейтронов. Предложенная технология является основой дальнейшей разработки органических детекторов большого диаметра для решения актуальных задач мониторинга окружающей среды, таможенного досмотра, проведения различных ядерно-физических экспериментов.